Detection of histamine 1 (H1) and histamine 2 (H2) receptors on murine spermatozoa by cellular and molecular studies / Nor Azimah Ahmad@Aziz - Nor Azimah , Ahmad@Aziz (2022)
Histamine is an important biogenic amine in various biological and physiological reactions which mediated by specific histamine receptors. The histaminergic studies in male reproductive system have been revived after the breakthrough of histamine synthesizing enzyme, histidine decarboxylase (HDC) was only found on male germ cell, spermatid acrosome, and spermatozoa, which has led to the ability of histamine synthesised in spermatozoa through in vitro acrosome reaction. There were significant studies reported on the negative effects upon histamine 1 (H1R) and histamine 2 (H2R) receptors antagonist administration on sperm parameters such as sperm count, motility, and sperm viability, herein speculates that H1R and H2R may be present on sperm. Therefore, this study aimed to detect H1R and H2R on murine sperm by cellular and molecular studies. The H1R and H2R localization on murine sperm was detected by immunocytochemistry technique. The sperm was smeared onto poly-lysine coated slide and allowed to dry prior to fixation and permeabilisation processes. The primary antibody encoded for receptors was exposed to fluorescently tagged antibody; fluorescein isothiocyanate (FITC) conjugate followed by nuclear staining with 4’, 6-diamino-2-phenylindole dihydrochloride (DAPI). The testis, stomach, and skin of mice were used as the positive control tissues, underwent the same procedures as sperm to verify the immunocytochemical evidence. In molecular study, sperm RNA was extracted by TRIzol method and reverse transcribed for complementary DNA (cDNA) synthesis prior to Polymerase Chain Reaction (PCR) for amplification of H1R and H2R genes which subsequently to detect the presence of the receptors molecularly. The purified DNA underwent DNA sequencing as a final verification step of study. Result showed that H1R and H2R were present on the midpiece and acrosome of epididymal sperm in cellular study and the presence of both receptors was supported by molecular evidence. The presence and immunolocalisation of H1R and H2R on the midpiece and acrosome coincide with the mapping of corresponding G-proteins on similar locations on mature sperm. The H1R-Gαq/11 and H2R-Gαs coupling initiate the signalling cascades through phospholipase C and adenylyl cyclase, respectively. Therefore, present study proposes that these receptors would be involved in calcium regulatory mechanism and protein phosphorylation which are responsible for fertilisation-related processes.